REAKSI PASAR TERHADAP PENGUMUMAN DIVIDEN KAS (Studi pada Perusahaan yang Terdaftar Di Bursa Efek Indonesia) - Iman Rafiyal Putra; Muhammad Arfan (Program Magister Akuntansi Unsyiah, 2013)
The purpose of this research is to obtain empirical evidence of how the average abnormal stock returns before and after the announcement of cash dividend, whether announcements of increasing cash dividend, constant cash dividend, and decreasing cash dividend on listed companies at the Indonesia Stock Exchange.This research uses census method. The research population are 51 companies. Abnormal return is measured based on individual stock returns using market returns. Individual stock return is obtained from the daily closing price and market return is measured using the Composite Index of BEI. The results show that: (1) the average abnormal stock return 10 days after the announcement of increasing cash dividends s is not higher than the average abnormal stock return 10 days before the announcement of increasing cash dividend (0.00460 0.00519), (2) the average abnormal stock return 10 days after the announcement of constant cash dividends is not higher than the average abnormal stock return 10 days before the announcement of constant cash dividend (0.00098 0.01617), (3) the average abnormal stock return 10 days after the announcement of decreasing cash dividend is not lower than the average abnormal stock return 10 days before the announcement of decreasing cash dividend (0.00151 0.00026). The conclusion of this research is that the announcement of cash dividend does not give abnormal return to investors. Keywords: Dividend announcement, abnormal return, increasing cash dividend, constant cash dividend, and decreasing cash dividend